Stepping stones as metaphor for building partnerships and co-producing knowledge in coastal transitions - Sørensen, Janni; Ounanian, Kristen; Jacobsen, Rikke Becker; Ekstedt, Josefin; Solnør, Sunniva Midthaug; Rønningen, Katrina; Gómez, Sílvia; Hadjimichael, Maria; Flannery, Wesley; Svels, Kristina; Antonova, Anna; Steiro, Vida Maria Daae; et al. (Taylor & Francis, 2025)
This paper centers local processes for co-creating transitions toward more sustainable, inclusive, and resilient coastal community development. We have conceptualized a path for change processes with phases of transition including 1. Reasons to convene; 2. Governance and participation “rules”; 3. Building knowledge together; 4. Implementing and experimenting; 5. Post-hoc reflections and assessment; 6. Transfer/reproduction of practices. Here, we focus on the first three stepping stones, which form the foundation of the collaborative process, focusing on the challenges and opportunities encountered as a pilot intervention is planned. We use a framework informed by partnership-, co-creation-, transition-, and justice literatures, to analyze data focused on establishing partnerships for ongoing co-creation of knowledge, empowering actors in the local communities, and selecting options for an intervention pilot. Conclusions relate to (a) trust and preexisting relationships, (b) what inclusion means, (c) internal power differentials, (d) preexisting tensions in the community, (e) challenges to co-creation.
Keywords: coastal transition; community development; participation; conflict; power